SEASONAL VARIATIONS OF THE PHYTOPLANKTON IN ALWND RIVER – IRAQ - ISMAIL, ABBAS M.; HASSAN, FIKRAT MAJEED (Iraqi Journal of Aquaculture, 2022)
The seasonal variations in algal compositions quantitatively and qualitatively have been studied for two stations in Alwnd River, represented before and after passing Khanqeen city through eight months starting in December 2000. A total of 123 phytoplankton taxa were identified, dominated by diatoms (63 species) followed by greens (34 species), blue-greens (15 species) and 11 species for other groups. The total cell number of phytoplankton ranged between 34565 and 37940 cell/cm3 in both stations with two peaks in spring and summer. The higher density of cell number and species was recorded in the second station during the studied period.